2013
DOI: 10.1016/j.febslet.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of novel chondroitin lyase ODV‐E66, a baculovirus envelope protein

Abstract: a b s t r a c tChondroitin lyases have been known as pathogenic bacterial enzymes that degrade chondroitin. Recently, baculovirus envelope protein ODV-E66 was identified as the first reported viral chondroitin lyase. ODV-E66 has low sequence identity with bacterial lyases at <12%, and unique characteristics reflecting the life cycle of baculovirus. To understand ODV-E66's structural basis, the crystal structure was determined and it was found that the structural fold resembled that of polysaccharide lyase 8 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…However, despite their homology, PmNV034 and PmNV036 have different lengths, relatively low identity and similarity (38% and 53%, respectively), and the hydrophobic INM-sorting sequence was found only in PmNV036 and not in PmNV034. AcMNPV ODV-E66 has also recently been shown to act as a chondroitin lyase [44]. Interestingly, both PmNV034 and PmNV036 contain all five of the conserved catalytic residues that are found in AcMNPV ODV-E66, suggesting that either or both of these proteins might function as a chondroitin lyase.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite their homology, PmNV034 and PmNV036 have different lengths, relatively low identity and similarity (38% and 53%, respectively), and the hydrophobic INM-sorting sequence was found only in PmNV036 and not in PmNV034. AcMNPV ODV-E66 has also recently been shown to act as a chondroitin lyase [44]. Interestingly, both PmNV034 and PmNV036 contain all five of the conserved catalytic residues that are found in AcMNPV ODV-E66, suggesting that either or both of these proteins might function as a chondroitin lyase.…”
Section: Resultsmentioning
confidence: 99%
“…We identified PrDs in 56 out of 66 known species belonging this family, indicating that this high prevalence of PrDs in one viral family may not be a coincidence. Therefore, we further showed that one of the PrDs associated with the cell adhesion and entry most frequently found in Baculoviridae is occlusion-derived virus envelope protein 66 (ODV-E66), which was recently the first identified viral chondroitin lyase, an enzyme that degrades chondroitin and is associated with viral entry 65,66 .…”
Section: Discussionmentioning
confidence: 97%
“…The results of x-ray crystallography studies pertaining to GAG eliminase and its enzyme-substrate complexes have allowed for the molecular mechanisms of polysaccharide degradation to be elucidated, as well as providing information concerning the potential direction of the reaction (16,22,36,37,39). However, the lack of conclusive evidence to support the direction of this process means that the direction currently remains unclear, which is primarily due to a lack of appropriate homologous model substrates.…”
Section: Resultsmentioning
confidence: 99%